Iconoclasm and the museum - Boldrick, Stacy, author.
1 online resource
Keywords: "Iconoclasm and the Museum addresses the museum's historic tendency to be silent about destruction through an exploration of institutional attitudes to iconoclasm, or image breaking, and the concept's place in public display. Presenting a selection of focused case studies, Boldrick examines long-standing desires to deface, dismantle, obscure or destroy works of art and historic artefacts, as well as motivations to protect and display broken objects. Considering the effects of iconoclastic practices on artworks and cultural artefacts and how those practices are addressed in institutions, the book examines changing attitudes to the intentional destruction of powerful artworks in the past and present. It ends with an analysis of creative destruction in contemporary art making and proposes that we are entering a new phase for museums, in which they acknowledge the critical roles destruction and loss play in the lives of objects and in contemporary political life. Iconoclasm and the Museum will be important reading for academics and students in fields such as museum and gallery studies, archaeology, art history, arts management, curatorial studies, cultural studies, history, heritage and religious studies. The book should also be of great interest to museum professionals, curators and collections management specialists, and artists"--